PENGARUH STRUKTUR MODAL, KEBIJAKAN DIVIDEN DAN PROFITABIITAS TERHADAP NILAI PERUSAHAAN - Marli, Marli; Anjarweni, Vika Atinia; Pudjiastuti, Widanarni (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2024)
Abstract, This study aims to investigate the impact of Capital Structure, Dividend Policy, and Profitability on the Firm Value of companies listed on the Indonesia Stock Exchange (IDX) within the LQ45 Index. The primary objective is to ascertain whether the assessment of these variables significantly influences Firm Value. A purposive sampling technique was employed to select a sample of 24 companies across various sectors for analysis. Quantitative data analysis was conducted using SPSS (Statistical Package for Social Science). The findings indicate that Capital Structure does not exhibit a significant effect on Firm Value, while Dividend Policy and Profitability both demonstrate a statistically significant impact. Moreover, the combined effect of Capital Structure, Dividend Policy, and Profitability significantly influences Firm Value.